Pelayanan dan Keuangan: Suatu Upaya Meningkatkan Keuangan Gereja dalam Mendukung Pemberitaan Kabar Baik di Calon Resort GKE Bulik Timur (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Many churches face great challenges in carrying out the mission of the gospel effectively in the midst of their limited resources, one of which is the Evangelical Kalimantan Church (GKE), especially in the Calon Resort (Cares) of GKE Bulik Timur. This study uses a qualitative approach by examining the condition of objects naturally, where the researcher plays the role of a key instrument and the sampling technique is carried out by purposive sampling. The results of the study show that limited funds caused by the lack of spiritual health of congregation members are the main obstacle to service, especially in PKB mission activities and congregation formation. The low financial support of the congregation is influenced by the weak theological understanding of giving and the limited economic income of the congregation. To overcome this, the church implements various theological and responsible efforts and strategies, including through strengthening preaching, spiritual formation, and the development of productive investment in the form of oil palm plantations. This plantation business has proven to be able to be a sustainable solution in supporting church finances so that services can run more optimally.